Seismogenic nodes as a viable alternative to seismogenic zones and observed seismicity for the definition of seismic hazard at regional scale - Rugarli, Paolo; Vaccari, Franco; Panza, Giuliano (Vietnam Journal of Earth Sciences, 2019)
A fixed increment of magnitude is equivalent to multiply the seismic moment by a factor γEM related to the partial factor γq acting on the seismic moment representing the fault. A comparison is made between the hazard maps obtained with the Neo-Deterministic Seismic Hazard Assessment (NDSHA), using two different approaches: one based on the events magnitude, listed in parametric earthquake catalogues compiled for the study areas, with sources located within the seismogenic zones; the other uses the seismogenic nodes identified by means of pattern recognition techniques applied to morphostructural zonation (MSZ), and increases the reference magnitude by a constant amount tuned by the safety factor γEM.Using γEM=2.0, in most of the territory the two approaches produce totally independent, comparable hazard maps, based on the quite long Italian catalogue. This represents a validation of the seismogenic nodes method and a tuning of the safety factor γEM at about 2.